Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1136/annrheumdis-2013-eular.1852
|View full text |Cite
|
Sign up to set email alerts
|

SAT0126 Rate of Remission by Tocilizumab or Methotrexate Induction Therapy in Early Active Rheumatoid Arthritis: Results of the Tomera Trial.

Abstract: Background Tocilizumab (TCZ), as monotherapy and in combination with methotrexate (MTX), has been shown to be efficacious in RA patients with insufficient response to MTX. Similar beneficial effects of TCZ were observed in early rheumatoid arthritis (ERA) and in RA patients refractory to TNF inhibitors. We aimed to compare the remission rates in ERA patients treated with TCZ or MTX. Methods Eligible patients had a disease duration ≤2 years, were MTX-naive, and had active RA (DAS28 ≥3.2). Thirty (23 women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…45 46 Two studies showed that the clinical benefit of intensive therapy was not maintained after its withdrawal39 45 47 and three others showed a small difference between groups. The radiographic evaluation conducted in four trials revealed a significant structural benefit in only two trials 45…”
Section: Resultsmentioning
confidence: 99%
“…45 46 Two studies showed that the clinical benefit of intensive therapy was not maintained after its withdrawal39 45 47 and three others showed a small difference between groups. The radiographic evaluation conducted in four trials revealed a significant structural benefit in only two trials 45…”
Section: Resultsmentioning
confidence: 99%
“…In this year’s (2013) European League Against Rheumatism (EULAR) meeting, two trials that aimed to study the role of TCZ exclusively in early RA population were presented 24,25…”
Section: Clinical Benefits Of Early Intervention With Tczmentioning
confidence: 99%
“…У пациентов, достигших стойкой ре-миссии (не менее 6-12 мес) на фоне комбинированной те-рапии МТ и ГИБП, возможно снижение дозы или отмена ингибиторов ФНОα [251][252][253][254][255][256][257][258][259][260][261][262], ТЦЗ [263][264][265], АБЦ [266] и РТМ [267]; при обострении возобновление терапии ГИБП в большинстве случаев позволяет достигнуть ремис-сии без развития резистентности к лечению. Рекомендация 24.…”
Section: поддержано рекомендациями Eular [9] междуна-родного консенсunclassified